Pathways of cell-cell transmission of HTLV-1 - Pique, Claudine; Jones, Kathryn S. (Frontiers in Microbiology, 2012)
The deltaretroviruses human T-cell lymphotropic virus type 1 (HTLV-1) and human T-cell lymphotropic virus type 2 (HTLV-2) have long been believed to differ from retroviruses in other genera by their mode of transmission. While other retroviruses were thought to primarily spread by producing cell-free particles that diffuse through extracellular fluids prior to binding to and infecting target cells, HTLV-1 and HTLV-2 were believed to transmit the virus solely by cell-cell interactions. This difference in transmission was believed to reflect the fact that, relative to other retroviruses, the cell-free virions produced by HTLV-infected cells are very poorly infectious. Since HTLV-1 and HTLV-2 are primarily found in T cells in the peripheral blood, spread of these viruses was believed to occur between infected and uninfected T cells, although little was known about the cellular and viral proteins involved in this interaction. Recent studies have revealed that the method of transmission of HTLV is not unique: other retroviruses including Human Immunodeficiency virus (HIV) are also transmitted from cell-to-cell, and this method is dramatically more efficient than cell-free transmission. Moreover, cell-cell transmission of HTLV-1, as well as HIV, can occur following interactions between dendritic cells and T cells, as well as between T cells. Conversely, other studies have shown that cell-free HTLV-1 is not as poorly infectious as previously thought, since it is capable of infecting certain cell types. Here we summarize the recent insights about the mechanisms of cell-cell transmission of HTLV-1 and other retroviruses. We also review in vitro and in vivo studies about infection and discuss how these finding may relate to the spread of HTLV-1 between individuals.